Penerapan Restorative Justice Dalam Pengungkapan Kasus Penganiayaan Di Kepolisian Resort Dairi - Feri Pasu Manaek Galingging; Ridho Zulyadi; Wessy Trisna (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Implementation of the principle of restorative justice on the crime of persecution is still many pros and cons. For the investigator is not easy to settle the criminal act of persecution with the principle of restorative justice because there must be agreement between the victim's family and the perpetrator. Research method in writing this thesis is Library Research and Field Research. Implementation of the principle of restorative justice in the process of investigation of children as perpetrators of criminal acts of persecution, investigators have opinions that are different from the Law of the Criminal Justice System of Children. Implementation of the principle of restorative justice in the settlement of criminal acts of mistreatment committed by a child is performed after the process of conversion if the diversion fails and without the existence of a third warning letter and the determination of the court. The obstacles faced by the Dairi Regional Police are that there is no meeting point between the perpetrators and the victims and their families, the families of the victims object to the perpetrators and expect the perpetrators to be punished severely, the victims and perpetrators do not want to make peace through diversion.